Effects of Drying Methods on the Aroma Components and Quality of Capsella Bursa‐Pastoris L. Issue 2 (3rd March 2015) - Zhang, Li; Liu, Tengfei; Xue, Yanjun; Liu, Chen; Ru, Hua; Dong, Minghui; Yu, Zhifang
Abstract: C apsella bursa‐pastoris L. ( C . bursa‐pastoris ) was treated by hot air drying, microwave drying, vacuum drying and freeze‐drying, respectively, to analyze the influences on aroma components using gas chromatography‐mass spectrometry. The results showed that the freeze‐dried product enjoyed significantly alleviated color changes, short rehydration time, high rehydration ratio and retention rates of chlorophyll and vitamin C. Vacuum drying functioned inferior to freeze‐drying but superior to hot air drying and microwave drying. As for aroma components, both vacuum drying and freeze‐drying managed to preserve the characteristic aroma components in C . bursa‐pastoris . In summary, vacuum drying and freeze‐drying retained the color, texture, morphology as well as grass and leaf aromas of C . bursa‐pastoris in maximum, but the former method, which lasts a shorter time and consumes less energy, should be given first priority in large‐scale industrial practice. Practical Applications: C . bursa‐pastoris suffers from a plummet of nutritional value and loss of economic benefits even within short harvest and storage periods. Drying newly harvested C . bursa‐pastoris with appropriate techniques can both meet different consumer demands and effectively prolong the shelf life of products. Various drying techniques are bound to affect sensory attributes and retention rates of nutrients and aroma components significantly. We treated fresh C . bursa‐pastoris by vacuum drying, hot air drying, microwave drying and freeze‐drying, and compared the quality of final products, aiming to find out the optimum drying method and parameters and while providing valuable practical evidence for industrial drying of this vegetable.